Central Neuropathic Pain and Profiles of Quantitative Electroencephalography in Multiple Sclerosis Patients - Krupina, Nataliya A.; Churyukanov, Maxim V.; Kukushkin, Mikhail L.; Yakhno, Nikolay N. (Frontiers in Neurology, 2020)
Pain has a significant impact on the quality of life of patients with multiple sclerosis (MS). We hypothesized that changes in power spectral density (PSD) that take place in the EEG of MS patients with and without the central neuropathic pain (CNP) would differ. The study aimed to assess the features of quantitative EEG using the PSD indicator along with peak frequencies in the standard frequency bands in MS patients with and without CNP. We have analyzed the quantitative spectral content of the EEG at a resting state in 12 MS patients with CNP, 12 MS patients without CNP and 12 gender- and age-matched healthy controls using Fast-Fourier-Transformation. Based on the ANOVA, at the Group level, the theta band absolute and relative PSD showed an increase whereas alpha band relative PSD showed a decrease in MS patients both with and without CNP. However, only in MS with CNP group, the absolute and relative PSD in the beta1 and beta2 bands increased and exceeded that in patients without pain. Only MS patients with CNP demonstrated the significantly increased absolute PSD for the theta, beta1, and beta2 frequency bands in most regions of interest. In the theta band, MS patients with CNP displayed the increase in absolute spectral power for the mid-temporal derivation of the right hemisphere and the increase in relative spectral power for the pre-frontal derivation of this hemisphere. In the beta1band, the increase in absolute spectral power was observed for the three temporal derivations of the right hemisphere whereas in the beta2-band, – for the occipital, parietal and temporal lobes of both hemispheres. In the alpha band, only relative spectral power decrease was revealed for the occipital lobes of both hemispheres and parietal lobe of the right hemisphere. In MS patients with CNP, the frequencies of the dominant spectral power (peak frequencies) in the high-frequency beta band were higher than in the healthy control in posterior areas of the left hemisphere. Data could represent central nervous system alterations related to central neuropathic pain in MS patients that lead to the disturbances in cortical communication.